Pitch as the Main Determiner of Italian Lexical Stress Perception Across the Lifespan: Evidence From Typical Development and Dyslexia - Caccia, Martina; Presti, Giorgio; Toraldo, Alessio; Radaelli, Anthea; Ludovico, Luca Andrea; Ogliari, Anna; Lorusso, Maria Luisa (Frontiers in Psychology, 2019)
The study deals with the issue of lexical stress perception in both a developmental (comparing children and adults with typical development) and a clinical perspective (comparing typically developing children and children with dyslexia). The three parameters characterising the acoustic profiles of words and nonwords in a certain language are duration, pitch and intensity of its syllables. Based on (sparse) previous literature on Italian and other European languages, it was expected that syllable duration would be the parameter predominantly determining the perception of stress position. It was furthermore anticipated that children with dyslexia may be found to have an altered perception of lexical stress, due to their impairments in auditory processing of either pitch, duration or (more controversial) intensity. Systematic manipulation of the pitch, duration and intensity profiles of three Italian trisyllabic nonwords produced a series of 81 stimuli, that were judged with respect to stress position (perceived on the ultimate, penultimate or antepenultimate syllable) by the three groups of participants. The results showed, contrarily to expectations, that the pitch component is the most reliable acoustic cue in stress perception for both adults, in whom this dominance is very strong, and typically developing children, who showed a similar but quantitatively less marked pattern. As to children with dyslexia, they did not seem to rely on any parameter for their judgments, and rather gave random responses, which point to a general inability to process the various acoustic modulations that normally contribute to stress perception. Performance on the stress perception task strongly correlates with language (morphosyntactic) measures in the whole sample of children, and with reading abilities in the group with dyslexia, confirming the strict relationship between the two sets of skills. These findings seem to support a language-specific approach, suggesting that the set of acoustic parameters required for the development of stress perception is language-dependent rather than universal.